Contribuição a uma teoria da extrafiscalidade na Política Nacional de Resíduos Sólidos - Silva, Rafaela Patricia Inocencio da (2018)
This dissertation intends to deal with the National Policy on Solid Waste (NPSW), a policy that was developed to provide an integrated management of solid waste through Law nº 12.305/2010. However, due to the few advances in this policy, it is necessary to use some instruments capable of giving more effectiveness to this legislation. Thus, it was decided to apply the taxes to stimulate environmentally appropriate activities related to management as well as to waste management. In this way, an extrapolation tool is visualized in the extrafiscality of the tribute for the realization of NPSW. The present research aims at the study of extrafiscality of taxes as a legal instrument for the protection of the environment and the promotion of sustainability in the scope of NPSW. The general problem of the dissertation was basically the analysis of extrafiscality as a means capable of assisting in the implementation of the National Policy on Solid Waste. The research method chosen for this work was the Environmental Rationality that is approached by Enrique Leff, and the research technique employed was indirect documentation. Finally, bibliographic research was also used.